Factors that lead to employee engagement at Sense Services Sdn. Bhd. / Nurul Aini Samsudin and Nur Syahira Bahman - Samsudin, Nurul Aini; Bahman, Nur Syahira (Faculty of Business and Management, 2012)
Employee engagement is one of the famous issues faced by organization nowadays. The purpose behind this paper is to figure out what variables impacting employee engagement, to comprehend their employment and profession desires and whether these elements are being impacted their engagement with the organization. The research reported in this paper is based on the questionnaire circulated to the employees of Sense Services Sdn. Bhd. It serves to figure out if Rewards and Recognitions, Work-life Balance, Internal Communication and Career Development & Opportunities have effects on employee engagement. This examination endeavors to analyze the hidden components that impact employee engagement. The total numbers of 69 employees were selected from Management Department, Human Resource Department, Account/Admin Department, Safety & Quality Department and Operation Department. The data were collected through distribution questionnaire survey and interpreted into readable and informative data through Reliability Analysis, Descriptive Analysis and Pearson’s Correlation.